3r-s=t

Simple and best practice solution for 3r-s=t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3r-s=t equation:


Simplifying
3r + -1s = t

Solving
3r + -1s = t

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add 's' to each side of the equation.
3r + -1s + s = s + t

Combine like terms: -1s + s = 0
3r + 0 = s + t
3r = s + t

Divide each side by '3'.
r = 0.3333333333s + 0.3333333333t

Simplifying
r = 0.3333333333s + 0.3333333333t

See similar equations:

| x(4-6)= | | 87/0.01 | | 4x+3x+x-1=2x-7 | | 4x+3=2x+x-3 | | t=sqrt(2-4x^2) | | 4x+3x+1=2x+6 | | 4cos^2x-11cosx+6=0 | | 4x+14=10x+2 | | (12x-3)(x+6)= | | x+(x-9)=101 | | 4(3m+1)-2(2m+3)=3(m+4)+2+7 | | (8m+3n)(2m+5n)= | | 4x+9=10x+5 | | x^4+11x^2-900=0 | | (8m+3n)(x+6)= | | 2sec(x)tan(x)=0 | | 35-k= | | -2x^2+16x-40=0 | | 4x+11=7x+5 | | 2x+9=7x+3 | | 3/4x8x | | (4a+8x)(7a-5x)= | | -1(x-y)+3(y-x)= | | (2w+2b)(3w+5b)= | | (ln(4)^2/(2ln2)-(ln(2)^2)/(2ln2) | | 30=3x-9 | | 2lnx-6=0 | | -5=0.25(4t+20r)-8r | | 1-4x/2x-1 | | 8sinx+16=20 | | t(2+-5t+3t^2)=0 | | 8+3x=x |

Equations solver categories